ЕФЕКТ ВИТІСНЕННЯ ТА ЙОГО ВПЛИВ НА МАСШТАБИ КРЕДИТУВАННЯ ЕКОНОМІКИ БАНКІВСЬКОЮ СИСТЕМОЮ УКРАЇНИ - Шпигоцька, Наталія Олегівна (Науковий журнал «Світ фінансів», 2017)
Шпигоцька Н. О. Ефект витіснення та його вплив на масштаби кредитування економіки банківською системою України. Розкрито проблему вияву ефекту витіснення в національній економіці. Виявлено масштаби реалізації ефекту витіснення через аналіз динаміки портфеля ОВДП у банківській системі України. Проаналізовано динаміку портфеля ОВДП та структуру активів банківської системи України. Доведено, що на сьогодні ефект витіснення має обмежений вплив на обсяги кредитування національної економіки через низьку частку ОВДП у портфелі комерційних банків в Україні. Шпигоцкая Н. О. Эффект вытеснения и его влияние на масштабы кредитования экономики банковской системой Украины. Раскрыто проблему проявления эффекта вытеснения в национальной экономике. Выявлено масштабы реализации эффекта вытеснения путем анализа динамики портфеля ОВГЗ в банковской системе Украины. Проанализировано динамику портфеля ОВГЗ и структуру активов банковской системы Украины. Доказано, что на сегодня эффект вытеснения имеет ограниченное влияние на объемы кредитования национальной экономики из-за относительно низкой доли ОВГЗ в портфеле коммерческих банков в Украине. Shpyhotska N. The effect of displacement and its impact on the scale of lending to the economy by the banking system Ukraine. Introduction. Recent growth in sovereign debt observed in Ukraine, that was accumulated, inter alia, via placement of domestic government bonds, creates a material concern for national economy. With additional debt results in higher debt servicing costs for the state budget, crowding out effect from placement of domestic bonds implies another concern for stimulating longterm economic growth in Ukraine. Purpose. To discover current magnitude of crowding out effect in Ukraine by studding local banks’ government bonds portfolio dynamics. Results. The government bonds portfolio dynamics in Ukraine, as well as banks’ assets structure were studied in order to determine, whether investments in state debt instruments constitutes a material portion of assets in banking system in Ukraine. With sovereign bonds account for a material portion of state banks’ assets, material volumes of banks’ assets invested in such bond are considered as being withdrawn from bank’s lending activity and thus limit lending volumes available for private enterprises in Ukraine. The historical dynamics of placement of local sovereign bonds in Ukraine was analyzed. Official statistics imply that as of early 2014 local bond accounted for about 50% of total sovereign debt in Ukraine, while about 70% of such local bonds were held by National Bank of Ukraine, 21% more – by Ukrainian commercial banks, and only 9% were held outside of Ukrainian banking system. Still, even though commercial banks held over 20% of sovereign local bonds, total bonds’ stock accounted for only 10% of total assets in banking system of Ukraine. Moreover, almost 60% of sovereign bond held by Ukrainian commercial banks were held by three state-owned banks, constituting a 35% share of their combined assets value. Net of aforementioned three state-owned banks, local sovereign bonds accounted for only 6% of total assets value of Ukrainian corporate banks. Conclusion. The study proves only limited magnitude of crowding out effect in national economy thus far due to low share of domestic government bonds in total bank’s assets volume. That said, we see no material negative implications for banks’ lending volumes from investing in sovereign debt instruments in Ukraine and thus preventing corporate lending in Ukraine.